2021
DOI: 10.2217/nnm-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Drug Vectors for Precise Cancer Treatment

Abstract: Extracellular vesicles (EVs) are nano-sized vesicle structures secreted from a variety of cells, which carry numerous biological macromolecules, participate in cell signal transduction and avoid immune system clearance. EVs have a plethora of specific signal recognition factors, and many studies have shown that they can play an important role in the precise treatment of tumors. This review aims to compile the applications of EVs as nanocarriers for antitumor drugs, gene drugs and other nanomaterials with antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 126 publications
0
16
0
Order By: Relevance
“…In particular, the method of imparting functions to EVs that are extracted by manipulating the cells described above is significantly different from the DDS technology that is applied to conventional artificial nanoparticle preparations. It was also revealed that CpG DNA-modified EVs showed a strong anti-tumor immune response by reacting with biotin derivatives of CpG DNA, which is an immunostimulatory nucleic acid, with the EVs modified by the fusion of protein with streptavidin showing binding to biotin and lactadherin, which is an EV-migrating protein [117,127].…”
Section: Modification Of Evs As Dds Methodsmentioning
confidence: 99%
“…In particular, the method of imparting functions to EVs that are extracted by manipulating the cells described above is significantly different from the DDS technology that is applied to conventional artificial nanoparticle preparations. It was also revealed that CpG DNA-modified EVs showed a strong anti-tumor immune response by reacting with biotin derivatives of CpG DNA, which is an immunostimulatory nucleic acid, with the EVs modified by the fusion of protein with streptavidin showing binding to biotin and lactadherin, which is an EV-migrating protein [117,127].…”
Section: Modification Of Evs As Dds Methodsmentioning
confidence: 99%
“…Although PTX has a low water solubility in clinical applications, it is frequently dissolved in Cremophor EL and ethanol to increase solubility. Cremophor EL, on the other hand, can produce hypersensitivity responses, such as hyperlipidemia and red blood cell aggregation, and permanent sensory neuropathy in the long run [267]. In a study, researchers encapsulated PTX in milk-derived exosomes and produced continuous PTX release for up to 48 h while maintaining optimal drug stability.…”
Section: Drug Delivery Vehiclementioning
confidence: 99%
“…Plant-derived EVs were evaluated for their therapeutic activities towards tumor cells and their abilities to be used as drug carriers. These EVs were extracted from edible plants [71]. Only recently did plant-derived EVs enter the recruitment processes for clinical trials.…”
Section: Plant-derived Evsmentioning
confidence: 99%
“…( 5) It is established that EVs could pass the BBB, giving an advantage in treating brain tumors. ( 6) Due to EVs' ability to circulate the blood, the drug's effect can last longer in the system [71].…”
Section: Application Of Evs As a Therapeutic Or Drug Delivery Agentmentioning
confidence: 99%
See 1 more Smart Citation